2021
DOI: 10.1080/1744666x.2021.1915770
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of T follicular helper cells in peripheral blood of rheumatoid arthritis patients: a systematic review and meta-analysis

Abstract: Objectives: Follicular helper T (Tfh) cells have critical roles in the development and promotion of humoral immune responses. Accumulating evidence points to alterations in the levels and activity of Tfh which may lead to impaired immune tolerance and development of antibody-mediated autoimmune diseases, such as rheumatoid arthritis (RA). To elucidate the status of Tfh cells in patients with RA, we conducted a systematic review and meta-analysis to assess the proportion and types of Tfh cells in the PB of RA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Rheumatoid arthritis (RA) is a prevalent chronic autoimmune disease characterized by synovial inflammation and joint cartilage destruction, resulting in joint deformity and disability [24]. It was found that the proportion of cTfh cells in RA patients was significantly higher than that in healthy people [25] and the Tfh cells are increased in the synovium of patients with RA compared with patients with inflammatory osteoarthritis [26]. The frequencies of circulating CD4 + CXCR5 + CD40L + Tfh cells, a Tfh cell subpopulation, are positively correlated with disease activity score-28 with erythrocyte sedimentation rate (DAS28-ESR), rheumatoid factors (RFs), and anticyclic citrullinated peptide (anti-CCP) autoantibodies, which are of great significance in the pathogenesis of RA [27].…”
Section: Tfh and Rheumatoid Arthritismentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a prevalent chronic autoimmune disease characterized by synovial inflammation and joint cartilage destruction, resulting in joint deformity and disability [24]. It was found that the proportion of cTfh cells in RA patients was significantly higher than that in healthy people [25] and the Tfh cells are increased in the synovium of patients with RA compared with patients with inflammatory osteoarthritis [26]. The frequencies of circulating CD4 + CXCR5 + CD40L + Tfh cells, a Tfh cell subpopulation, are positively correlated with disease activity score-28 with erythrocyte sedimentation rate (DAS28-ESR), rheumatoid factors (RFs), and anticyclic citrullinated peptide (anti-CCP) autoantibodies, which are of great significance in the pathogenesis of RA [27].…”
Section: Tfh and Rheumatoid Arthritismentioning
confidence: 99%
“…As such, it has been proposed that an expanded pathogenic CD4 + T-cell population mediates activation of autoreactive B cell recognizing post-translationally modified self-antigens and resulting in the production of matured autoantibodies directed towards these autoantigens ( 4 , 5 ). These processes typically occur in germinal centers of lymphoid tissues and involve a well characterized population of T follicular helper cells (Tfh) expressing CXCR5 and PD-1 ( 6 ). Of considerable interest has been the demonstration of a distinct population of activated CD4+ T cells, both in the blood and the affected synovial tissues, characterized by PD-1 hi CXCR5 - expression, and labelled as peripheral-helper T cells (Tph cells) ( 7 ).…”
Section: Introductionmentioning
confidence: 99%